Producing Cellulose from Straw : Opportunities in Ukraine - International Finance Corporation (Kiev, 2014)
This report is based on research conducted throughout 2011–2012 in cooperation with Ukrainian agricultural producer Mriya Agro Holding to assess the country’s potential for producing cellulose from straw. The objective of this report is to demonstrate – for the country’s decisionmakers, agribusinesses, paper-industry players and financial institutions – how Ukraine’s available supply of straw could be efficiently used to produce paper and cardboard, through the implementation of a major straw-tocellulose program.